A Fully Magnetically Levitated Circulatory Pump for Advanced Heart Failure - Mehra, Mandeep R; Naka, Yoshifumi; Uriel, Nir; Goldstein, Daniel J; Cleveland, Joseph C; Colombo, Paolo C; Walsh, Mary N; Milano, Carmelo A; Patel, Chetan B; Jorde, Ulrich P; Pagani, Francis D; Aaronson, Keith D; et al. (The New England journal of medicine, 2017)
In a randomized trial, 294 patients with advanced heart failure were assigned to receive either a new centrifugal-flow pump or an axial-flow pump. At 6 months, the centrifugal-flow pump was associated with better outcomes. A scarcity of effective therapeutic options for advanced heart failure has led to the development of durable mechanical circulatory support devices. Left ventricular assist devices, more accurately known as left ventricular assist systems, increase the rate of survival and improve quality of life among patients with advanced heart failure. However, these clinical benefits are balanced by an increased risk of infection, bleeding, neurologic events, and pump malfunction that is due principally to pump thrombosis. 1 , 2 As adoption of circulatory pumps has expanded, concerns about pump thrombosis have heightened. In 2013, two reports suggested that there has been an increase in . . .